Agronomic Responses of Soybean (Glycine max L. Merrill) to Spent and Deoiled Bleaching Earth Filler-Based NPK Fertilization - Muhammad Parikesit Wisnubroto; Eka Tarwaca Susila Putra; Budiastuti Kurniasih (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
The objective of the study was to study the effects of spent bleaching earth (SBE) and deoiled bleaching earth (DBE) filler-based NPK fertilizers on the agronomical characteristics of soybean as a model crop. A field experiment was arranged in a single factor of randomized complete block design (RCBD) with four blocks as replications. The treatments were 1) NPK fertilizer with 10% of BC (control), 2) NPK fertilizer with 5% of BC + 5% of SBE, and 3) NPK fertilizer with 5% BC + 5% DBE. The variables observed were the levels of heavy metals in leaf tissue and the agronomic characteristics of soybean plants. The observations were made on several variables of agronomical crop characters. The data were then analyzed with analysis of variance (ANOVA) at 5% levels and continued with the Least Significant Difference (LSD) test if there were differences among treatments. The results confirmed that the SBE and DBE materials could partly replace the filler components in NPK fertilizers, which has been proven to have the same impact on the agronomical characteristics of soybean in the form of leaf area, root volume, number of pods per plant, number of seeds per plant, and seed yield per hectar.